Islamic Legal Review of Waqf Land Ownership Transfer under Indonesian Law - Siti Chadijah; Muhammad Rifqi Rifai; Muhammad Abdul Zalil (UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to analyse the Islamic legal position on the transfer of ownership of waqf land and evaluate its conformity with the Indonesian waqf regulatory framework. Using a normative-juridical method, the research examines classical and contemporary fiqh references, Law No. 41 of 2004, Government Regulation No. 42 of 2006, and relevant legal documents to construct a systematic interpretation of the rules governing waqf property. The analysis identifies the legal basis for the prohibition of transferring waqf assets and assesses the coherence between sharia norms and national regulation. The results reveal that Islamic jurisprudence categorically upholds the permanence of waqf property, while practices at the administrative level remain vulnerable to irregularities, particularly in certification and oversight procedures. Weak institutional verification allows waqf assets to be at risk of being transferred or re-registered contrary to their legal status. This study contributes an evaluative framework for aligning Islamic legal principles with positive law and proposes policy improvements, including stronger cross-institutional verification and enhanced supervisory mechanisms to prevent unauthorised transfers of waqf assets.